Chalice and Blade: Dreaming a Partnership Future - Jonee Kulman Brigham (Interdisciplinary Journal of Partnership Studies)
A new poem titled “Chalice and Blade” imagines how a partnership future might be envisioned as it grows from our partnership and domination history. The author describes the poem’s influences, including its primary inspiration that came from the ideas and themes in Riane Eisler’s seminal book, The Chalice and the Blade: Our History, Our Future.